Using artificial intelligence for sustainable crop production – a comprehensive review with a focus on potato production - Magdalena Piekutowska (Journal of Water and Land Development)
The article discusses the critical role of artificial intelligence (AI) in modern agriculture, with a particular focus on potato production. AI technologies are becoming essential tools enhancing both efficiency and sustainability in farming practices. By utilizing big data analysis, precision monitoring, and automation, AI can significantly improve agricultural outcomes. For instance, AI algorithms can optimise the use of natural resources and chemical inputs, leading to improved yield forecasting and more effective management of diseases and pests that affect crops. Additionally, AI can play a key role in agriculture with is its capability to monitor soil conditions and assess soil fertility. This enables farmers to optimise fertilisation techniques, leading to improved crop health but also better water management through precise irrigation practices. These advancements are especially crucial in addressing the rising food demand posed by global population growth, while simultaneously managing limited environmental resources. Despite the numerous benefits offered by AI, its implementation in agriculture faces challenges. High technology costs and the need for extensive education and training for farmers can hinder widespread AI adoption. Therefore, future research should aim at developing affordable AI solutions and comprehensive training programmes to maximise the technology's potential in fostering enhanced sustainable food production globally.